Analysis of the Application of Government Regulation No.23 of 2018, Understanding of Taxation and Tax Sanctions Against MSMEs Taxpayer Compliance - Jenny Jenny; Ronaldy Andika Putra Telaumbanua (eCo-Fin, 2020)
The purpose of this study was to determine the effect of Government Regulation No. 23 of 2018, Understanding of Taxation and Tax Sanctions on MSMEs Taxpayer Compliance in Plaza Harmoni, Tangerang City. The application of Government Regulation (PP) Number 46 of 2013 is one of the government's efforts to improve tax compliance for MSMEs. Besides, the government has also provided tax penalties for taxpayers who do not pay taxes. Data analysis techniques using multiple linear regression analysis methods, the sample in this study was 100 respondents. The results showed a T value of X1= 4.723, X2 = 3,975, and X3 = -0.033. It means that the application of PP 23 of 2018, understanding taxation, and Tax sanctions had a positive and significant effect on Msme's taxpayer compliance